2022
DOI: 10.1002/advs.202105571
|View full text |Cite
|
Sign up to set email alerts
|

Kartogenin‐Conjugated Double‐Network Hydrogel Combined with Stem Cell Transplantation and Tracing for Cartilage Repair

Abstract: The effectiveness of existing tissue-engineering cartilage (TEC) is known to be hampered by weak integration of biocompatibility, biodegradation, mechanical strength, and microenvironment supplies. The strategy of hydrogel-based TEC holds considerable promise in circumventing these problems. Herein, a non-toxic, biodegradable, and mechanically optimized double-network (DN) hydrogel consisting of polyethylene glycol (PEG) and kartogenin (KGN)-conjugated chitosan (CHI) is constructed using a simple soaking strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…53 A recent study reported that MSCs maintained chondrocyte-like morphology in a KGN-conjugated hydrogel scaffold after culturing for 14 days. 54…”
Section: Resultsmentioning
confidence: 99%
“…53 A recent study reported that MSCs maintained chondrocyte-like morphology in a KGN-conjugated hydrogel scaffold after culturing for 14 days. 54…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used KGN as a bioactive agent to induce chondrogenic differentiation. Many articles have demonstrated that KGN has the ability to significantly promote cartilage regeneration, and it is stable, easy to transport and store, is an ideal bioactive factor. ,, We combined it with SilMA hydrogels to achieve a continuous release of KGN while creating a mechanical environment for cartilage. Our results indicate that SilMA/KGN hydrogels has a significant ability to promote cartilage regeneration both in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, KGN is a promising molecule for inducing cartilage regeneration. A series of articles have shown that KGN can effectively promote chondrogenic differentiation of stem cells. …”
Section: Introductionmentioning
confidence: 99%
“…32,33 These unique intrinsic features could be applied for drug delivery and tissue regeneration, so fibrin-based hydrogels could be designed by adjusting the components and concentrations of the precursors, including fibrinogen and thrombin. 34–37 In addition, numerous studies have reported that kartogenin (KGN), as a nonprotein small molecule drug, could significantly promote cartilage-specific gene expression in BMSCs in a dose-dependent manner without any toxicity. 38–42 Most importantly, a certain level of reactive oxygen species (ROS) in the tissue microenvironment could promote BMSC proliferation and induce differentiation into chondrocytes by stimulating the secretion of glycosaminoglycan.…”
Section: Introductionmentioning
confidence: 99%